Effect of river indus sand on concrete tensile strength - Lakhiar, Muhammad Tahir; Mohamad, Noridah; Shaikh, Muhammad Abu Bakar; Ahmed Vighio, Anees; Ahmed Jhatial, Ashfaque; Abdul Samad, Abdul Aziz (Engineering, Technology and Applied Science Research (ETASR), 2018)
In the development of Pakistan construction industry, the utilization of River Indus sand in concrete as fine aggregate has expanded tremendously. The aim of this research is to study the effect of Indus River sand on the tensile strength of various grades of concrete when it is utilized as fine aggregate. Concrete Samples of M15, M20 and M25 grade concrete were cured for 7, 14, 21 and 28 days. Based on the results, it is found that concrete became less workable when Indus river sand was utilized. It is recorded that tensile strength of concrete is decreased from 5% up to 20% in comparison with hill sand. The results were derived from various concrete grades.